The Role of Shadow Teachers For Supporting Learning Assistance on Children with Special Needs in Inclusive Early Childhood Education - Uswatun Nisa; Anwar Zain; Aulia Rahmah (Journal of Islamic Education Students (JIES), 2024)
Inclusive education is an implementation of the international consensus of providing education for all. Every child is given the rights as a citizen, including the right to access adequate and quality education. Inclusive education rejects dichotomies and discrimination because children are seen as having equal dignity and worth. Likewise with children with special needs such as autism, down syndrome, attention deficit hyperactivity disorder and other physical, mental and neurological obstacles. Differences in treatment encourage the presence of accompanying teachers for children with special needs at every school level. This qualitative study uses a narrative descriptive approach to explore the importance of accompanying teachers in supporting learning assistance for children with special needs. Data was obtained through field observations, interviews and documentation of 4 accompanying teachers with social work laboratory backgrounds and 2 class teachers at the school. The findings were obtained in conjunction with the data analysis process by the author as the main research instrument, seeing that accompanying teachers reflect each child's profile to accommodate needs, support learning and improve children's self-development skills activities.